PROGRAM PENGEMBANGAN “PROTAP” (PRODUK DARI TANAMAN ASLI PAPUA) SEBAGAI PROGRAM PEMBERDAYAAN EKONOMI BIDANG KESEHATAN PADA MASYARAKAT KAMPUNG TOBATI-ENGGROS KOTA JAYAPURA - Puguh Sujarta; Septriyanto Dirgantara (JURNAL PENGABDIAN PAPUA, 2018)
Indonesia is a country that has a wealth of flora number two in the world after Brazil and is believed to have a variety of plants tha can be used as medicine.The use of herbs fo treatment, especially the use of medicines that have been integrated into formal health services in Indonesia is still low compared to some other Asian countries.  Papuan medicinal plants have superior characteristic that are different from other provinces in Indonesia. The usage of potential natural products as medicines for Papuan communities are selected by a good  understanding of herbal medicine. The potential of biological acticity from  natural resources provides a great opportunity to developing this program. In this case, the activities of the Community Engagement activities with the title Development of "PROTAP" (Products of Medicinal Plants of Papua) for the community in Tobati-Enggros Village of Jayapura City; first introducing the potential for development of traditional medicine; secondly practicing the manufacture of PROTAP (products from the Papuan Native Medicinal Plant) and positively impacting the economic development of communities in the utilization of local Papuan products; the third produces an output in the form of local and national community engagement journals. The methods used in the implementation of this activity are lectures, simulations or demonstrations as well as the direct practice of manufacturing products from indigenous plant drugs Papua. The conclusion that tarticipants are very enthusiastic to follow the activity of service and can know the development program of PROTAP, Based on the evaluation result indicates that the participants have satisfaction level is high when viewed from percentage of all aspect.Keywords: PROTAP, Economy, Community, Tobati-Enggros